Association of life’s essential 8 and inflammatory biomarkers with nutritional anemia in UK adults - Jingjing Wang; Xueting Qi; Guozheng Wang; Weijing Wang; Dongfeng Zhang (Scientific Reports)
Abstract Several modifiable health factors in Life’s Essential 8 (LE8) are linked to nutritional anemia and can assess overall cardiovascular health (CVH). This study explored the associations of CVH measured by LE8 score with nutritional anemia and iron deficiency anemia (IDA), including the mediating role of inflammatory biomarkers. This prospective cohort study included 181,069 participants from UK Biobank. CVH was categorized into low (0–49), medium (50–79), and high (80–100) based on the LE8 score. Weibull regression models were used to quantify the association between CVH and nutritional anemia and IDA. During a median follow-up of 8.6 years, 6749 cases of nutritional anemia occurred, including 92% (6223/6749) IDA cases. After adjusting for covariates, participants with moderate CVH and high CVH had a 44% and 54% lower risk of nutritional anemia (Moderate: hazard ratio [HR] 0.56; 95% confidence interval [CI], 0.51–0.60; High: HR 0.46; 95% CI, 0.41–0.51), and a 46% and 54% lower risk of IDA (Moderate: HR 0.54; 95% CI, 0.50–0.59; High: HR 0.46; 95% CI, 0.41–0.51), respectively, compared to those with low CVH. An L-shaped association was observed between CVH score and both types of anemia. Inflammatory biomarkers explained 22.1% and 21.6% of the associations between CVH and nutritional anemia and IDA, respectively. Higher CVH scores were associated with lower risk of nutritional anemia and IDA, and these associations may be partially mediated by inflammatory biomarkers. These findings emphasize the importance of CVH and inflammation in preventing nutritional anemia.